Dyeing characteristics and functionability of tussah silk fabric with oak bark extract. Issue 15 (September 2017) - Jia, Yanmei; Liu, Bo; Cheng, Dehong; Li, Jia; Huang, Fang; Lu, Yanhua
In order to realize the ultraviolet (UV) protection property and antimicrobial activity simultaneously, as well as the natural dyeing process, oak bark extract was prepared and applied to dye tussah silk fabric. The effects of dyeing pH value, temperature, time and mordant kinds on dyeing properties of tussah silk fabric were analyzed. The results indicated that the optimum direct dyeing conditions were as follows: pH 5.0, temperature 98℃, time 80 min. As for the mordant dyeing process, the K / S values of the post-mordant dyed samples were higher than those of the pre-mordant dyed samples. The color of the direct, aluminum potassium sulfate, copper sulfate and the ferrous sulfate dyed samples were brown, yellow-brown, dark brown and gray black, respectively. The washing, rubbing and light fastness of the three mordants dyed samples were all good. Moreover, the dyed samples showed an excellent UV protection property and antimicrobial activity. The UV protection factor values of the mordant dyed sample were more than 40; the reduction in bacterial count percent against S. aureus and E. coli reached up to and above 85% and 80%, respectively; and the weight gain rate was more than 6%. Furthermore, the dyed samples had good washing durability of the UV protection function and antimicrobial activity even after 50 consecutive launderings.